PERKEMBANGAN JUMLAH DAN KAPABILITAS BANK SAMPAH TAHUN 2015 - 2020 ( STUDI KASUS PADA BANK SAMPAH ZONA 2C / SEGMEN 4 CITARUM ) - Muhamad Diva Nugraha, - (2021)
The waste bank is one of the relatively new breakthroughs in waste management. However, until now the development and capability of the Waste Bank has not been well mapped. Based on this, it is known that the waste bank study is very important because it can help reduce waste in the future. Therefore, the purpose of this study is to analyze the development of its number, distribution and capabilities.. The research method uses a descriptive quantitative approach. The results of this study indicate that there is an increase in the number of waste bank units from 5 units to 28 units in the period 2015 - 2020. The distribution of waste bank locations is random and covers the scope of around RW. The capacity and volume of waste bank units increases every year along with the number of waste bank units operating.. The conclusion is that the development of the number has increased in the period 2015 - 2018 and has decreased in 2019 - 2020, the distribution is in accordance with the location where it was established, capabilities have increased significantly in the span of 3 years, but the last 2 years have decreased. The research implication is that the waste bank unit program is made more attractive in conducting socialization, providing guidance on escorting the implementation process, increasing support through funding, supervision, and facilitating all the needs of the waste bank unit. Keywords: Development, Amount, Capability, Waste Bank Unit